INFECTION RATE OF TOXOPLASMOSIS IN ANGORA GOATS OF DUHOK PROVINCE-IRAQ - Nawzat A. Issa (Basrah Journal of Veterinary Research)
In this study the seroprevalence of active toxoplasmosis represented by T. gondii IgM in angora goats was detected in Zakho and Semel districts of Duhok provinceIraq for the first time. T. gondii antibodies were detected at the laboratory of college of Veterinary Medicine of Duhok University from April 2009 to May 2010. Ninety two (92) serum samples were collected from clinically healthy adults’ angora goats (54 and 38 were obtained from Semel and Zakho, respectively). Indirect Enzyme Linked Immunosorbent Assay was applied and the overall infection rate was %13.04. Results show that the infection rate was different between the two regions with a higher rate recorded in Zakho. Female and older animals were affected with higher infection rates than males and younger animals. It can be concluded that toxoplasmosis is an active infection among angora goats of Duhok province, therefore145